A reappraisal of the relationship between arachnoid cysts of the middle fossa and chronic subdural haematoma. Issue 8 (August 1987) - Page, A; Paxton, R M; Mohan, D
Abstract : It has been increasingly recognised that patients with arachnoid cysts of the middle fossa appear more susceptible to the development of subdural haematomas. Seven patients with arachnoid cysts of the middle fossa and associated subdural haematomas are presented. Intra-cystic haemorrhage, masking the presence of an arachnoid cyst on computed tomography (CT) is highlighted. Repeat of CT scanning in young patients with subdural haematomas in the absence of severe trauma is recommended. Two theories are proposed to account for the observed susceptibility to the development of subdural haematomas in these patients.